The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2141/jpsa.0120169
|View full text |Cite
|
Sign up to set email alerts
|

Production of n-3PUFA Enriched Eggs By Feeding Various Dietary Ratios of n-6 to n-3 Fatty Acids and Vitamin A Levels to the Laying Hens in Hot Climate

Abstract: In the present study, the effect of various dietary ratios of linoleic acid (LNA) to α-linolenic acid (ALA), and vitamin A (Retinyl Acetate) on egg quality and some blood metabolites was examined in laying hens kept at high ambient environmental temperature. Three hundred and sixty laying hens were fed rations supplemented with different combinations of canola oil and linseed oil to have LNA to ALA dietary ratios of 20:1, 10:1, 4:1, 2:1, 1:1 and 1:2, each with 3000 IU or 10000 IU vitamin A/kg of diet (6×2 fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…There was a significant ( p < 0.05) interaction between fat source and the level of inclusion in the diet, and LNA content was increased when hens were fed diets with linseed and rapeseed oil (30 g/kg diet). In contrast, da Silva Filardi et al [90] studied the effects of the dietary inclusion (for 12 weeks) of different fat sources (cottonseed oil, soybean oil, lard, SO, or canola oil) on egg quality, and egg yolk lipid profiles. The different fat sources did not affect eggshell quality; however, the lipid profile of the egg yolk changed based on dietary fat sources.…”
Section: Improving Egg Quality and Nutritional Value Of Eggsmentioning
confidence: 99%
“…There was a significant ( p < 0.05) interaction between fat source and the level of inclusion in the diet, and LNA content was increased when hens were fed diets with linseed and rapeseed oil (30 g/kg diet). In contrast, da Silva Filardi et al [90] studied the effects of the dietary inclusion (for 12 weeks) of different fat sources (cottonseed oil, soybean oil, lard, SO, or canola oil) on egg quality, and egg yolk lipid profiles. The different fat sources did not affect eggshell quality; however, the lipid profile of the egg yolk changed based on dietary fat sources.…”
Section: Improving Egg Quality and Nutritional Value Of Eggsmentioning
confidence: 99%
“…There is no study investigating the effect of varying farming temperatures on the enrichment process with n‐3 FA. However, a study reported successful enriching eggs through flaxseed oil and canola oil in HT‐farmed hens (Ahmad et al, 2014). When we compare our data with treatments with the same range of linoleic acid: A‐linolenic acid ratio on their study, similarly, n‐3 FAs increased with the elevation of flaxseed oil (Ahmad et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…However, a study reported successful enriching eggs through flaxseed oil and canola oil in HT‐farmed hens (Ahmad et al, 2014). When we compare our data with treatments with the same range of linoleic acid: A‐linolenic acid ratio on their study, similarly, n‐3 FAs increased with the elevation of flaxseed oil (Ahmad et al, 2014). Recently, the disrupting effect of HT on lipid metabolism in poultry was reviewed for temperatures higher than 30°C (Emami et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…There was a significant (p < 0.05) interaction between fat source and the level of inclusion in the diet, and LNA content was increased when hens were fed diets with linseed and rapeseed oil (30 g/kg diet). In contrast, [14], studied the effects of the dietary inclusion (for 12 weeks) of different fat sources (cottonseed oil, soybean oil, lard, SO, or canola oil) on egg quality, and egg yolk lipid profiles.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%